Final covers for solid waste landfills and abandoned dumps - Koerner, Robert M., 1933- (ASCE Press ; Thomas Telford, 1997)
Presents the essential elements for the design of final covers for solid waste landfills and abandoned dumps. This book gives an overview and presents selected aspects of regulations in the US and Germany, countries where the regulations are the most advanced. It also gives information on each of the six individual layers of final cover systems.